(untitled) (Our Nature, 2025)
The role of alien invasive plants on the interaction between native plants and soil has been a critical concern for understanding invasion mechanism and response of native plants towards invasion. This study aims to analyze the effect of invaded soils by an invasive Siam weed (Chromolaena odorata (L.) R.M. King & H. Rob.) under sterilized and unsterilized conditions on growth performance of seedlings of a valuable native Sal tree (Shorea robusta Gaertn. f.). For the analysis, seedlings of S. robusta were grown in pots and growth parameters were measured. Results showed that the C. odorata invaded soil reduces the root biomass, leaf length and leaf breadth of S. robusta seedlings. Sterilization of the invaded increased root and shoot and leaf size of the seedlings. In conclusion, soil sterilization can promote early-stage growth for S. robusta seedlings, adjusting with altering the shape and size of leaves in response to invasion. This suggests that soil microbes play an important role in negatively impacting native plants with invasion of C. odorata.